ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI ARITMATIKA SOSIAL - Isnawati Isnawati; Tina Rosyana (IKIP Siliwangi, 2021)
This type of research is a qualitative descriptive study that aims to analyze the mistakes of junior high school students in completing social arithmetic material. The subjects used were 20 students of class VIII-C SMP Sejahtera 2 Cileungsi, one of the private junior high schools in Bogor Regency. The data collection technique used was in the form of student test results with written questions in the form of descriptions of 5 questions, then each error faced by students was described in each question number on the social arithmetic material. The data analysis performed was data reduction, data presentation and conclusion drawing. The highest percentage of errors was in question number 4, which was 75%, while the lowest percentage of errors was in question number 2, which was 10%. Based on the results of the study, it showed that there were several mistakes in solving the essay questions, namely errors in understanding the basic concepts, errors in principle in reading the essay questions, and errors in operating the data contained in the questions. The conclusion from the results of this study obtained data that the ability of students still experienced many errors in solving social arithmetic questions.